2021
DOI: 10.1007/s00704-021-03800-z
|View full text |Cite
|
Sign up to set email alerts
|

Indoor temperature variability in the Sahel: a pilot study in Ouagadougou, Burkina Faso

Abstract: Very little research has documented the exposure of populations in Africa to extreme heat. We measured indoor air temperature and humidity hourly for 13 months in seven houses of contrasted architecture and construction materials all in the northern neighbourhoods of Ouagadougou, Burkina Faso. These measurements are compared to air temperatures recorded at the synoptic weather station of Ouagadougou airport and to land surface temperature estimates from Landsat satellite images at seven dates with clear-sky co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Some of the studies extracted found an association between higher temperatures and mortality [ 68 , 69 ], as well as an increase in mortality owing to cardiovascular diseases [ 70 ]. A pilot study in Burkina Faso found temperature variations between different types of housing units, with some types currently exceeding extreme danger levels of heat exposure [ 71 ]. Current literature shows a clear relationship between climate change impacts and increased exposure to hazardous temperatures in the Sahel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the studies extracted found an association between higher temperatures and mortality [ 68 , 69 ], as well as an increase in mortality owing to cardiovascular diseases [ 70 ]. A pilot study in Burkina Faso found temperature variations between different types of housing units, with some types currently exceeding extreme danger levels of heat exposure [ 71 ]. Current literature shows a clear relationship between climate change impacts and increased exposure to hazardous temperatures in the Sahel.…”
Section: Resultsmentioning
confidence: 99%
“…All of the studies regarding heat stress raised important concerns about increased mortality rates associated with heat waves and heat stress in the Sahel [65][66][67][68][69][70][71]. Increased exposure to hazardous temperatures could increase mortality and the prevalence of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%